A national health service : draft memorandum on the government's proposals
1944-04-14 1944 1940s 14 pages COPY PRIVATE AND CONFIDENTIAL NOT FOR PUBLICATION THE BRITISH HOSPITALS ASSOCIATION - A NATIONAL HEALTH SERVICE Draft Memorandum on the Government's Proposals. 1. - The Executive Committee of the British Hospitals Association has given careful consideration to the proposals of the government in regard to the establishment of a National Health Service, as outlined in the White Paper. The speeches of the government's spokesmen in the debates thereon which took place in the House of Commons and in the House of Lords have also been studied. The Executive Committee feels that it should now put on record its considered opinions on the several proposals contained in the White Paper which deal with the Hospital Service of the future. In the preparation of this memorandum the Association has acted in collaboration with King Edward's Hospital Fund for London. There have also been informal consultations with representatives of the British Hospitals Contributory Schemes Association and the British Medical Association,, and it is understood that these bodies are substantially in agreement with the principles herein advocated. Informal consultation has also taken place with the Nuffield Provincial Hospitals Trust. 2. - Desirability of Immediate Statement of Policy. The view has been expressed in some quarters that, inasmuch as the government has stated that the White Paper must be regarded rather as a basis for dicussion than as a final statement of its intentions, any official statement of policy by the Executive Committee of the Association now would be premature, and should be deferred until the outcome of such further discussions as the Minister has promised are known. It will, however, be remembered that, during the twelve months prior to the publication of the White Paper, informal discissions took place between the Minister and a deputation, representative of the voluntary hospitals and King Edward's Hospital Fund for London. In the course of these discussions emphatic representations were made by the voluntary hospitals that the interest of the patient must be the primary consideration in any National Health Service, and that this could only be achieved by a scheme in which the administrative structure, and the manner of the distribution of public monies, was such as would preserve the status of the voluntary hospitals and their freedom from State or Local Authority control, thus enabling them to continue efficiently their work of healing, and, as the primary centres of medical study and research, to make their full contribution to the efficiency of a comprehensive service. It is apparent from the White Paper, that these representations have been disregarded by the Ministry, which might give ground for the assumption that an attempt may be made to confine the further discussions promised to details only. For this reason, the Executive Committee regards it as imperative that the views of the voluntary hospitals on certain fundamental matters of principle shell be redefined. This memorandum has accordingly been prepared with a view to discussion with the Minister of Health when required. (contd.) 292/847/2/33